Значење на висината на серумските концентрации на прокалцитонинот во предвидување на текот и исходот кај пациенти со сепса во корелација со индексите на тежина на болест - Демири, Илир (Медицински факултет, УКИМ, Скопје, 2021)
Introduction - Sepsis is the leading cause of hospitalization in intensive care units, resulting in high morbidity and mortality. The possibility of identifying the outcome in patients with sepsis as soon as possible is vital. Procalcitonin (PCT) is a marker with good potential for diagnosing the progression and outcome of patients with sepsis and septic shock. The aim of the study was to evaluate the prognostic significance of serum procalcitonin values and kinetics in critically ill patients with sepsis and septic shock. Materials and methods- The research was prospective, group comparison and was performed in the intensive care unit at the Clinic for Infectious Diseases and Febrile Conditions in Skopje. The study included 100 patients over the age of 18 with clinical, laboratory-biochemical indicators in addition to sepsis and septic shock. The surveyed respondents were further divided into two subgroups: a group of survivors - 57 patients and a group of deceased - 43 patients. PCT values were measured in all patients at the time of admission to the clinic, after 24 and 48 hours, using the Enzyme Linked Fluoroscent Assay (ELFA) of the Mini Vidas Biomerieux apparatus. Values above 2 ng / ml are considered elevated. The degree of organ dysfunction was determined by the Sepsis-related Organ Failure Assessment score (SOFA) index, which was also determined at enrollment in the study, 24 and 48 hours later. The SOFA index ≥ 2 is also used to diagnose patients with sepsis. Results- The patients had a mean age of 54.3 ± 16.8 years. 32.00% of patients were female and 68.00% were male. The SOFA index in all patients was ≥ 2. Throughout the follow-up period, lower serum concentrations of procalcitonin were measured in the survivor group. According to the results, the area size below the ROC curve (AUC) for procalcitonin was 0.767, indicating a test with good discriminant ability in separating patients with and without sepsis, as well as predicting the severity and outcome of the disease. The sensitivity of the test is 62.5%, the specificity is 88%. Conclusion- Defining procalcitonin as a marker with good discriminatory ability in separating patients with and without sepsis, as well as predicting the severity and outcome of the disease, will have a significant implication for implementing an appropriate treatment protocol, thereby improving outcome and reducing of mortality from this disease, which is the main benefit of this dissertation.
Докторска дисертација одбранета во 2021 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Звонко Миленковиќ.
Keywords: sepsis, septic shock, procalcitonin, predicting the severity